2011
DOI: 10.1097/ipc.0b013e3182041e0a
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary Tuberculosis

Abstract: rom 1985 until 1992 there was a resurgence of tuberculosis in the United States that coincided with the epidemic of acquired immunodeficiency syndrome (AIDS). 1 Although the U.S. incidence of tuberculosis has since been in decline, this disease remains a major problem for much of the world, with a global prevalence of infection estimated at 32 percent. 2 Thus, the percentage of U.S. cases that occur among foreign-born persons is increasing (53 percent in 2003). 1 Extrapulmonary tuberculosis has become more com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
1
1
Order By: Relevance
“…Twenty-three lymph node aspirates and one body fluid specimens were also smear positive with Ziehl Neelsen staining technique. The cytological result of the current study was higher than the other studies conducted in Saudi Arabia (42.9%) and Ethiopia (39.7%) [26,27]. …”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Twenty-three lymph node aspirates and one body fluid specimens were also smear positive with Ziehl Neelsen staining technique. The cytological result of the current study was higher than the other studies conducted in Saudi Arabia (42.9%) and Ethiopia (39.7%) [26,27]. …”
Section: Discussioncontrasting
confidence: 89%
“…Previously, age was reported as an independent risk factor for EPTB infection in high-burden countries [26,32,33]. This is consistent with other studies in San Francisco, Saudi Arabia, India and Tanzania which showed that high prevalence of EPTB among productive age groups [26,28,30,34].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation